The Category of Fairness of a Taxpayer and Its Reflection in Law Enforcement Practice - KARMALITA, Mariia V.; IAKYMCHUK, Nataliia Ya.; KASIANENKO, Liubov M.; LUKASHEV, Oleksandr A.; ANDRUSHCHENKO, Halyna S. (Journal of Advanced Research in Law and Economics, 2019)
Based on the analysis of current trends in the implementation of legal regulation of public relations, the influence of the case law on the development of tax law is illustrated. The purpose of this study is to clarify the role of case law in the formation of the category of taxpayer fairness and accordingly the development of tax law. The concepts and varieties of judicial doctrines, elaborated in the context of balancing private and public interest in taxation, are defined. It is stated that the analysis of the practice of application of tax and legal doctrines indicates the creation of guarantees for the provision of private and public interests in taxation, which are manifested in the inadmissibility of arbitrary approaches to the analysis of case files, evaluation of evidence, the establishment of legally relevant facts, etc. Considerable attention has been paid to the category of taxpayer fairness. Approaches to its understanding in scientific circles as well as its use in law enforcement practice are analyzed.